Endoscopic evaluation of therapeutic effects of “Anuloma-Viloma Pranayama” in Pratishyaya w.s.r. to mucociliary clearance mechanism and Bernoulli's principle - Bhardwaj, Atul (Medknow Publications & Media Pvt Ltd, 2013)
The current endeavor intended to evaluate the effectiveness and mode of action of Anuloma-Viloma Pranayama (AVP), i.e., alternate nasal breathing exercise, in resolving clinical features of Pratishyaya, i.e., rhinosinusitis. The present study was directed to validate the use of classical “saccharin test” in measuring the nasal health by measuring mucociliary clearance time. This study also highlights the effects of AVP by application of Bernoulli principle in ventilation of paranasal sinuses and surface oxygenation of nasal and paranasal sinuses ciliary epithelium. Clinically, endoscopically and radiologically diagnosed patients of Pratishyaya, i.e., rhinosinusitis, satisfying the inclusion criteria were selected to perform AVP as a breathing exercise regularly for 30 min every day in order to evaluate the effectiveness of AVP in resolving features of rhinosinusitis. Saccharin test was performed before and after completion of 40 days trial to assess the nasal ciliary activity, which has been proved to be directly related to the health of ciliary epithelium and nasal health overall as well. AVP may be regarded as a catalyst to conspicuously enhance ventilation and oxygenation of the paranasal sinuses and the positively effect the nasal respiratory epithelium by increasing better surface availability of oxygen and negative pressure in the nasal cavity itself.